2009
DOI: 10.2355/isijinternational.49.1
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and Disarming of Drain Sink Formation during Unsteady-state Bottom Teeming

Abstract: The behavior of an unsteady-state drain sink as function of outlet diameter, outlet length, supernatant phase viscosity, supernatant phase density and supernatant phase layer thickness was studied using physical modeling. Two new hydrodynamic models for the prediction of the drain sink formation height were derived and compared to models found in literature. Both could accurately predict the drain sink formation height in their respective domain as function of all variables mentioned above, except supernatant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 9 publications
3
10
0
Order By: Relevance
“…At the late stage of a ladle teeming process, a drain sink flow phenomena of steel may result in slag entrainment. Although much effort has focused on this problem,1, 3, 7, 10, 12, 17, 18 there is still no an effective way to completely prevent the occurrence of a drain sink flow. However, methods that can reduce the residual steel before the drain sink phenomena occur should be favorable for obtaining a larger steel yield.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the late stage of a ladle teeming process, a drain sink flow phenomena of steel may result in slag entrainment. Although much effort has focused on this problem,1, 3, 7, 10, 12, 17, 18 there is still no an effective way to completely prevent the occurrence of a drain sink flow. However, methods that can reduce the residual steel before the drain sink phenomena occur should be favorable for obtaining a larger steel yield.…”
Section: Resultsmentioning
confidence: 99%
“…They can also decrease the steel product quality. Owing to the important influence of ladle teeming on both the steel cleanness and temperature, it received a great deal of research efforts,1–20 which is illustrated in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed knowledge of vortex mechanisms will essentially allow designing flow control devices aimed at minimizing slag carryover during vortex drain and sink drain flows. The difference between the present work and those of others [3][4][5][6][7][8][9][10][11][12][13][14][16][17][18][19][20] is the study of the contribution of buoyancy forces to enhance vortex drain mechanism. Here we use the approach of water modeling complemented with a mathematical-multiphase flow model under isothermal and non-isothermal conditions to perform deeper understanding of the transport phenomena involved during teeming-draining operations of liquid steel.…”
Section: Introductionmentioning
confidence: 88%
“…Both, experimental and numerical analysis show that sink drain takes place when the height of the steel column is approximately equal © 2013 ISIJ to the nozzle diameter. 1,10,[16][17][18] Some researchers claim that there is not early vortex formation and that slag carryover is observed only during the sink drain flow. 16,19,20) However, this is not in agreement with most of the experimental and numerical results [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] since other researchers report vortex drain development before the observation of sink drain flow.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, hand, a drain sink is characterized by the radial flow and develops in the last stage of the teeming process, when less liquid steel is left in the ladle. A drain sink is always present at the end of the process and takes place when the bath height of the steel is approximately equal to the nozzle diameter [4,6,16]. Several researchers claim that there was no vortex formation and slag carry-over was caused by drain sink in the teeming ladle [4,8], while more researchers reported that vortex was formed prior to the drain sink formation [1][2][3]7,17].…”
Section: Introductionmentioning
confidence: 99%